MODEL PENINGKATAN MINAT MENABUNG GENERASI Z DI BANK SYARIAH MELALUI MEDIA SOSIAL DAN EDUKASI DIGITA UNTUK PENGUATAN EKOSISTEM KEUANGAN - Putri Nazli; Siti Kadariah; Sakina Puspita Sari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The low interest of Generation Z in saving with Sharia banks poses a challenge to efforts aimed at strengthening the Sharia financial ecosystem in the digital era. As a demographic deeply integrated with technology and social media, Generation Z requires educational approaches that align with their digital-native characteristics. This study aims to analyze the factors influencing Generation Z's interest in saving with Sharia banks and to formulate a model for boosting this interest through the use of social media and digital education. The study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews with members of Generation Z and Sharia banking practitioners, Focus Group Discussions (FGDs), and observations of Sharia financial education content on social media. Data analysis was conducted using thematic analysis techniques to identify patterns, perceptions, and experiences regarding Sharia financial literacy and saving behavior. The findings indicate that Sharia financial literacy, digital education, and social media are the primary factors influencing Generation Z's interest in saving. The study proposes an integrative model linking these three factors to enhance saving interest and support the strengthening of the Sharia financial ecosystem in Indonesia. Keywords: Saving Interest; Generation Z; Islamic Banking; Social Media; Digital Education.   Abstrak: Rendahnya minat menabung Generasi Z pada bank syariah menjadi tantangan dalam upaya penguatan ekosistem keuangan syariah di era digital. Generasi Z sebagai kelompok yang sangat dekat dengan teknologi dan media sosial memerlukan pendekatan edukasi yang sesuai dengan karakteristik digital mereka. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi minat menabung Generasi Z pada bank syariah serta merumuskan model peningkatan minat menabung melalui pemanfaatan media sosial dan edukasi digital. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui wawancara mendalam terhadap Generasi Z dan praktisi perbankan syariah, Focus Group Discussion (FGD), serta observasi terhadap konten edukasi keuangan syariah di media sosial. Analisis data dilakukan menggunakan teknik analisis tematik untuk mengidentifikasi pola, persepsi, dan pengalaman informan terkait literasi keuangan syariah dan perilaku menabung. Hasil penelitian menunjukkan bahwa literasi keuangan syariah, edukasi digital, dan media sosial merupakan faktor utama yang memengaruhi minat menabung Generasi Z. Penelitian ini menghasilkan model integratif yang menghubungkan ketiga faktor tersebut dalam meningkatkan minat menabung serta mendukung penguatan ekosistem keuangan syariah di Indonesia. Kata kunci: Minat Menabung, Generasi Z, Bank Syariah, Media Sosial, Edukasi Digital.